MANAJEMEN KURIKULUM MERDEKA DI SD NEGERI 4 TULUNG SELAPAN KABUPATEN OGAN KOMERING ILIR - Muhammad, Muhammad; Harapan, Edi; Putra, Juliansyah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Education is essential for creating high-quality human resources. It is essential for everyone to maximize their potential and compete in the ever-changing dynamics of globalization. Education is very important to face the challenges and changes of the times that continue. The objectives of this study: 1) Describing the planning of the independent curriculum at SD Negeri 4 Tulung Selapan, Ogan Komering Ilir Regency; 2) Describing the implementation of the independent curriculum at SD Negeri 4 Tulung Selapan, Ogan Komering Ilir Regency; 3) Describing the evaluation of the independent curriculum at SD Negeri 4 Tulung Selapan, Ogan Komering Ilir Regency. This research is descriptive qualitative research. Data collection techniques through interviews, observation, and documentation. Sources of research data, Principal and Teacher of SD Negeri 4 Tulung Selapan totaling 3 teachers. Data analysis techniques are data reduction, data presentation and data verification. The results of this study that: 1) The planning of the independent curriculum at SD Negeri 4 Tulung Selapan, Ogan Komering Ilir Regency has been well implemented; 2) The implementation of the independent curriculum at SD Negeri 4 Tulung Selapan, Ogan Komering Ilir Regency has been carried out properly; 3) Evaluation of the independent curriculum at SD Negeri 4 Tulung Selapan, Ogan Komering Ilir Regency is well implemented.